Intention to use e-government services among the academic staff in Saudi universities - Khalid F, Alanazi Mujahed (2016)
E-government diffusion and usage is a global topic that concerns many countries worldwide. E-government is a way for providing services of government over online channels of communication to its citizens. Saudi Arabia has implemented a program of e-government in 2005 to encourage performance of public sectors through acquiring the benefits of Information Communication Technology (ICT) advances. This study focuses on the factors that influence intention to use e-government among the academic staff in Saudi Arabia. In addition, this study is to identify the mediating role of e-government awareness on the relationships between social influence, trust of internet and trust in intermediaries and intention to use e-government and the mediating role of perceived risk on the relationships between trust of internet and trust in intermediaries and intention to use e-government. Based on the Theory of Planned Behaviour (TPB), this study integrated these factors to examine their influences on intention to use e-government. This study utilized a quantitative approach using a survey to reflect consumers’ perspectives towards e-government usage. To examine the hypothesized model, the data were collected from the academic staff working in Saudi public universities. This study employed Partial Least Squares techniques to confirm the validity and reliability of the measurement model and to examine the structural relationships. The findings of the study confirmed the influences of social influence, e-government awareness, trust in intermediary and perceived risk on intention to use e-government. Further, awareness of e-government is influenced by social influence, trust in Internet and trust in intermediary and mediates the relationship between these factors and intention to use e-government. Trust in Internet factor emerged as significant predictor of consumers’ risk perceptions and mediates the relationship between this factor and intention to use e-government. This study has important implications for e-government practitioners, researchers and policy decision makers interested in the implementation of e-government